WOMEN’S RESISTANCE TOWARD DISCRIMINATION IN EGYPT IN THE NOVEL WOMEN AT POINT ZERO USING BOURDIEU PERSPECTIVE - Cut Novita Srikandi (Universitas Muhammadiyah Tangerang, 2018)
Abstract The issue of women's discrimination in the Middle East has become common knowledge. Injustice treatment of women in Middle Eastern countries occurs because of the patriarchal culture that still surrounds by most of society. The problem has been raised in various media, one of which is literary media. Through the novel entitled Women at PointZero by Nawal El Saadawi raises the reality of women discrimination experienced by most Middle Eastern women, especially in Egypt. Therefore, this research seeks to reveal the issue of discrimination of women raised by authors in the novel. Descriptive research method of analysis by using the approach Pierre Bourdieu related habitus, arena, capital and social practices used to reveal the factors that cause discrimination against female character in the novel. The end result of the study shows the social practice of Firdaus in countering the discrimination of women in Egypt against male patriarchal dominance in social space of society. Key words: Discrimination of women in Egypt, habitus, arena, capital, social practice